On looking [large type] : eleven walks with expert eyes - Horowitz, Alexandra (Center Point Large Print, 2013)
On looking : Eleven Walks with Expert Eyes is structured around a series of eleven walks the author takes with experts on a diverse range of subjects, including an urban sociologist, a well-known artist, a geologist, a physician, and a sound designer. She also walks with a child and a dog to see the world as they perceive it. What they see, and how they see it, reveals the startling power of human attention and the cognitive aspects of what it means to be an expert observer.